2019
DOI: 10.1044/2018_ajslp-18-0150
|View full text |Cite
|
Sign up to set email alerts
|

Dying for a Meal: An Integrative Review of Characteristics of Choking Incidents and Recommendations to Prevent Fatal and Nonfatal Choking Across Populations

Abstract: Purpose The purpose of this study was to conduct an integrative review of original research, across adult populations relating to fatal or nonfatal choking on food, to understand ways to respond to and prevent choking incidents. Method Four scientific databases (CINAHL, Medline, Web of Science, and EMBASE) were searched for original peer-reviewed research relating to fatal or nonfatal choking on foods. Data were extracted on study characteristics; facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 66 publications
0
36
0
2
Order By: Relevance
“…A recent integrative review of the research related to choking on food in adults identified that choking is associated with trauma and fear. 66 Interestingly, previous research on the experience of choking from the perspective of people with ALS concluded that only 27% of them perceived choking as moderately severely distressing whereas 73% perceived mild or no distress. 67 Caregivers’ fear of choking strongly emerged in our study and this may suggest that the caregivers experience more distress related to choking than the person with ALS.…”
Section: Discussionmentioning
confidence: 98%
“…A recent integrative review of the research related to choking on food in adults identified that choking is associated with trauma and fear. 66 Interestingly, previous research on the experience of choking from the perspective of people with ALS concluded that only 27% of them perceived choking as moderately severely distressing whereas 73% perceived mild or no distress. 67 Caregivers’ fear of choking strongly emerged in our study and this may suggest that the caregivers experience more distress related to choking than the person with ALS.…”
Section: Discussionmentioning
confidence: 98%
“…Factors which place individuals at risk of FBAO include psychotropic medication, alcohol intoxication, neurological conditions producing reduced swallowing and cough reflexes, mental impairment, developmental disability, dementia, poor dentition and older age. 138,139 Foreign bodies most commonly associated with airway obstruction are solids such as nuts, grapes, seeds, vegetables, meat and bread. 137,138 Children, in particular, may put all sorts of objects in their mouths.…”
Section: Recognitionmentioning
confidence: 99%
“…The death rate associated with choking is significantly and positively associated with aging (see Figure 1) have also reported choking as the second highest preventable cause of death in this cohort (1,5,6). This is due to several factors including, physiological changes to the body's musculature, poor dentition, dementia and other neurological comorbidities, which combined are estimated to increase the risk of choking sevenfold in people over the age of 65 (7,8). Another significant characteristic of choking is the high percentage of incidences caused by soft foods relative to large solid pieces, in contrast to younger populations (9).…”
Section: Foreign Body Airway Obstruction (Fbao)mentioning
confidence: 60%